Tratamento endovascular de aneurisma intracraniano residual ou recorrente após clipagem cirúrgica. - Nilton Rocha da Silva Júnior (2020)
Introduction: Embolization is increasingly used to treat intracranial aneurysms, as endovascular techniques have continued to improve. The total occlusion of the aneurysm is crucial for the prevention of rebleeding of a ruptured aneurysm or the subsequent growth, and to avoid rupture of an unruptured lesion. However, both surgical clipping and endovascular embolization fail to achieve complete aneurysm obliteration in the totally of the cases. Remnant aneurysms have a small, but significative risk of bleeding. Objectives: To evaluate occlusion, morbidity and mortality rates with the endovascular treatment of residual or recurrent intracranial aneurysms after surgical clipping. Materials and Methods: Was conducted an multicenter, retrospective and observational study to establish the safety and efficacy of the treatment endovascular incompletely clipped aneurysms, and to identify predictors of total aneurysm occlusion, recanalization and complications. The patients were divided into 4 groups according to the method of endovascular treatment used: 1) embolization with detachable platinum spirals (19); 2) embolization with detachable platinum spirals associated with the balloon remodeling technique (25); 3) embolization with detachable platinum spirals and stent implantation (8); 4) endovascular treatment with a flow diverter device (18). They were evaluated for their demographic data, type of diagnostic manifestation, characteristics of the aneurysms, complications of the procedure, morbidity and mortality, recanalization rate and recurrence of the treated aneurysms. Patients were studied immediately before and after treatment and then at 6 months and 1 year. Results: Seventy patients (80% female) were evaluated. most patients (84.3%) had unruptured aneurysms, diagnosed in a control angiogram, and 15.7% presented with subarachnoid hemorrhage. The modified Rankin Scale before treatment was 0 in 49 patients, 1 in 11 patients, 2 in 7 patients, and > 2 in 3 patients. The mean aneurysm size was 7.5 mm in diameter. The most frequent location was at the ophthalmic segment of the internal carotid artery (32.9%) and were located at a sidewall (70%) at the anterior circulation (92.9%). All aneurysms treated with flow diverter device (18/70) were completely occluded after 1 year. During the first year after treatment 1 (1.4%) patient, harboring a ruptured anterior communicating artery aneurysm died due to complications of vasospasm. Permanent morbidity occurred in 2 (2.9%) patients due to complications related to the subarachnoid hemorrhage (both with ruptured communicating segment aneurysms submitted to balloon remodeling treatment). Another 2 patients with ruptured aneurysms presented with transient morbidity not related to the treatment, but they fully recovered. Conclusion: Endovascular treatment of recurrent or residual aneurysms after surgical clipping was safe and efficacious. Flow diversion seems to be associated with better anatomical results. A more rigid study, a larger group of patients, and long-term follow-up are required to provide stronger conclusions about the better approach to residual clipped aneurysms.